Advocate to Win - Hansen, Heather (Ascent Audio, 2021)
Advocate to Win shares how you can use the tools of a trial attorney to ask for what you want-and get it. Publishers Weekly called Heather Hansen's first book, The Elegant Warrior, a "template for achieving personal and career goals." In Advocate to Win, Heather goes deeper. As an award-winning trial attorney, Heather quickly realized that she didn't win because she was an extraordinary advocate. She won because she gave her clients the tools to advocate for themselves. First, they needed to choose what they wanted. Next, they needed to believe in themselves and their ability to get it. And then, they could advocate to win. Heather created a system to help her clients make the best choices for themselves, for the case, and for their wins. She gave them the tools to believe. And then she gave them specific strategies to advocate for what they wanted and to win with ease. Now, she will do the same for you.